Injury and health risk management in sports. A guide to decision making (Springer, 2020)
This book is a comprehensive source of information and guidance on health risk management and medical care across the entire range of sports, in athletes of all ages and ability. General health aspects, injury prevention, first aid and emergency management, diagnosis, treatment, rehabilitation, and return to play are all addressed, with presentation of practical recommendations throughout. All medical disciplines with relevance for athletes - from psychological aspects to dermatological issues - are as well as main pathologies, overuse injuries and indications for surgical treatment of all certain parts of the musculoskeletal system, covered.